The hospital ethical climate survey in Turkey - (:unkn) unknown (My University, 2003)
This study was planned to assess the validity and reliability of the Hospital Ethical Climate Survey (Olson, 1995) in Turkey and to determine how nurses perceive the ethical climate of their working environment. The study was conducted on 276 nurses working in university, social insurance, state, and private hospitals. Five subfactors measured: assessment of the relationships between unit/department, manager, hospital, colleague, and doctors based on ethical climate. Significant differences were found, showing that the type of hospital greatly affected the level of positive perception as did the age of the nurse and the unit on which they worked. © 2003 Lippincott Williams & Wilkins, Inc.